The Effect of Different Doses of Aerobic Exercise Training on Total Bilirubin Levels - Swift, Damon L. (2012)
Low serum bilirubin levels have been associated with increased risk for cardiovascular disease, and recent data suggest that lower body fat and reductions in weight are associated with higher bilirubin levels. However, it is unknown if exercise training can increase bilirubin levels and whether a higher dose of exercise will further increase bilirubin levels compared to a lower dose. PURPOSE: The primary aim of our current report is to examine whether exercise dose affects bilirubin levels in obese postmenopausal women from the Dose Response to Exercise in Women (DREW) trial. In addition, we evaluated whether changes in fitness, insulin sensitivity, and waist circumference associated with exercise training were associated with change in bilirubin levels. METHODS: Participants (n= 419) were randomized to the control group or 4, 8 and 12 kilocalories per kilogram per week (KKW) of exercise training at an intensity of 50% of aerobic capacity. Total bilirubin levels were evaluated at baseline and at follow-up. RESULTS: Exercise training significantly increased serum bilirubin levels only in the 12 KKW group (0.044 mg/dL, p=0.026) compared to control (0.004 mg/dL). Subgroup analyses showed that there was a significant increase in bilirubin levels in participants in the 12 KKW group (0.076 mg/dL) who were classified as insulin resistant (HOMA> 2.6), compared to insulin resistant control participants (0.018 mg/dL) (p=0.028). CONCLUSION: Our findings suggest that high doses of exercise training are necessary to significantly increase bilirubin levels in previously sedentary postmenopausal women especially in individuals with impaired glucose metabolism.